Editorial. Issue 1 (1st March 2019) - Kowalsky, Sharon A.
Abstract : As we begin Volume 13, Aspasia would like to take this opportunity to congratulate several of our contributors. First, congratulations to Rochelle Ruthchild on her receipt of the Association of Women in Slavic Studies Outstanding Achievement Award (see the citation "In Recognition: Rochelle Goldberg Ruthchild" following this introduction). In addition, Emily Gioielli's article, "'Home Is Home No Longer': Political Struggle in the Domestic Sphere in Postarmistice Hungary, 1919–1922, " which appeared in Volume 11 (2017), received an honorable mention for the 2018 Mark Pitt away Article Prize in Hungarian Studies by the Hungarian Studies Association. Aspasia is pleased to extend its congratulations to Rochelle and Emily.